Cellular and genetic models of H6PDH and 11β‐HSD1 function in skeletal muscle. (27th July 2017) - Zielinska, Agnieszka E.; Fletcher, Rachel S.; Sherlock, Mark; Doig, Craig L.; Lavery, Gareth G.
Abstract : Glucocorticoids are important for skeletal muscle energy metabolism, regulating glucose utilization, insulin sensitivity, and muscle mass. Nicotinamide adenine dinucleotide phosphate‐dependent 11β‐hydroxysteroid dehydrogenase type 1 (11β‐HSD1)‐mediated glucocorticoid activation in the sarcoplasmic reticulum (SR) is integral to mediating the detrimental effects of glucocorticoid excess in muscle. 11β‐Hydroxysteroid dehydrogenase type 1 activity requires glucose‐6‐phosphate transporter (G6PT)‐mediated G6P transport into the SR for its metabolism by hexose‐6‐phosphate dehydrogenase (H6PDH) for NADPH generation. Here, we examine the G6PT/H6PDH/11β‐HSD1 triad in differentiating myotubes and explore the consequences of muscle‐specific knockout of 11β‐HSD1 and H6PDH. 11β‐Hydroxysteroid dehydrogenase type 1 expression and activity increase with myotube differentiation and in response to glucocorticoids. Hexose‐6‐phosphate dehydrogenase shows some elevation in expression with differentiation and in response to glucocorticoid, while G6PT appears largely unresponsive to these particular conditions. When examining 11β‐HSD1 muscle‐knockout mice, we were unable to detect significant decrements in activity, despite using a well‐validated muscle‐specific Cre transgene and confirming high‐level recombination of the floxed HSD11B1 allele. We propose that the level of recombination at the HSD11B1 locus may be insufficient to negate basal 11β‐HSD1 activity for a protein with a long half‐life. Hexose‐6‐phosphate dehydrogenase was undetectable in H6PDH muscle‐knockout mice, which display the myopathic phenotype seen in global KO mice, validating the importance of SR NADPH generation. We envisage these data and models finding utility when investigating the muscle‐specific functions of the 11β‐HSD1/G6PT/H6PDH triad.